2015
DOI: 10.1002/jcb.25149
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Oxidative Stress Response in HepG2 Cells Following Acute and Prolonged Exposure to Antiretroviral Drugs

Abstract: Chronic HIV treatment with antiretroviral drugs has been associated with adverse health outcomes. Mitochondrial toxicity exhibited by nucleoside reverse transcriptase inhibitors (NRTIs) is pinpointed as a molecular mechanism of toxicity. This study evaluated the effect of NRTIs: Zidovudine (AZT, 7.1 μM), Stavudine (d4T, 4 μM) and Tenofovir (TFV, 1.2 μM), on mitochondrial (mt) stress response, mtDNA integrity and oxidative stress response in human hepatoma cells at 24 and 120 h. Markers for mt function, mt biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…This effect in cells is related to DNA lesions induced directly by NAs incorporated into genomic DNA, or indirectly by targeting telomerase or ROS-induced oxidative damage. [35][36][37][38][39][40][41][42][43][44][45][46] The phosphorylation occurs soon after DNA damage and accumulates around the break site to attract proteins involved in repair and chromatin remodeling. We found that the level of gH2AX is much greater in both cell lines infected with latent HIV-1, than in un-infected cells, when they were exposed to high concentrations of the NRTI-type of NAs that we tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect in cells is related to DNA lesions induced directly by NAs incorporated into genomic DNA, or indirectly by targeting telomerase or ROS-induced oxidative damage. [35][36][37][38][39][40][41][42][43][44][45][46] The phosphorylation occurs soon after DNA damage and accumulates around the break site to attract proteins involved in repair and chromatin remodeling. We found that the level of gH2AX is much greater in both cell lines infected with latent HIV-1, than in un-infected cells, when they were exposed to high concentrations of the NRTI-type of NAs that we tested.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed DDR by exposing cells to high doses of the anti-HIV class of NAs called nucleoside reverse transcriptase inhibitors (NRTIs), choosing AZT (azidothymidine, zivudine) and d4T (stavudine), which are known to incorporate into genomic DNA, affect telomerase and to induce oxidative stress. 36,[38][39][40][41][42][43][44][45][46] The effects of high doses of NRTIs on DNA damage response in latent cells were analyzed by assessing the level of gamma-H2AX (gH2AX), which is a biomarker of DSBs. The gH2AX protein is a histone H2A variant, H2AX, phosphorylated on serine 139 in response to DSBs.…”
Section: Ddr In Latently Infected Cells Responds Less Efficiently To mentioning
confidence: 99%
“…Zidovudine treatment has also been shown to reduce the rate of oxygen consumption in human umbilical vein endothelial cells (HUVEC) (Jiang et al , 2007), in adipocytes (3T3-F442A white and T37i brown) (Viengchareun et al , 2007), and in vascular smooth muscle cells (VSMC) (Hebert et al , 2004). Further, zidovudine inhibits respiration of mitochondria from rat skeletal muscle and brain (Modica-Napolitano, 1993), and has been shown to lower cellular ATP levels (Nagiah et al , 2015; Viengchareun et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…impaired maximal mitochondrial respiration and SRC) represents a common pathway by which these ARV drugs may initiate neuronal dysfunction. Several of the ARV drugs tested here have been shown previously to dissipate the mitochondrial membrane potential, including efavirenz (Blas-Garcia et al , 2014; Funes et al , 2014; Jin et al , 2016; Purnell and Fox, 2014), emtricitabine (Groener et al , 2011), indinavir (Jiang et al , 2007), lopinavir (Groener et al , 2011), and zidovudine (Caron et al , 2004; Jiang et al , 2007; Nagiah et al , 2015). The mitochondrial membrane potential is a central regulator of cell health, it provides the charge gradient required for mitochondrial calcium sequestration and ATP generation, and also regulates ROS production (Perry et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation